Sound insulation and hydrophobic properties of phenolic resin modified melamine foam: role of micro-morphology. (24th April 2019) - Yang, Yong; Chen, Zhou; Xu, Tengzhou; Han, Ruonan; Emefa Awuye, Desire
Abstract: In this paper, physical properties (sound insulation and hydrophobicity) and corresponding mechanism of melamine foam (density 8 kg m −3 and thickness 18 mm) modified by phenolic resin were explored. Results showed that deposits of phenolic resin were found on the foam skeleton and formed various morphologies between the skeletons. These morphologies were seen in different forms such as 'plane', 'spherical' and 'flat' depending on the phenolic resin content. This phenomenon had a significant effect on the pore size of melamine foam. There was a remarkable improvement in sound transmission loss (STL) compared to that without phenolic resin. However, STLs did not increase monotonically. The contact angles of all samples modified by phenolic resin were around 1300, presented a slight fluctuation due to pore size and exhibited excellent hydrophobic property.